ANALISIS HUKUM ISLAM TERHADAP TRADISI PEUTRON ANEUK DALAM ADAT ACEH - Ariesman M; Nurfiah Nurfiah; Rosalia Oktafia (AL-ASHLAH : Jurnal Hukum Keluarga dan Hukum Islam, 2025)
This study aims to analyze the perspective of Islamic law on the Peutron Aneuk tradition, a cultural practice in Aceh, particularly in Desa Paya Peunaga, Kecamatan Meureubo, Kabupaten Aceh Barat. The research addresses two main issues: (1) How is the ritual process of the Peutron Aneuk tradition conducted in Desa Paya Peunaga, Kecamatan Meureubo, Kabupaten Aceh Barat? and (2) What is the perspective of Islamic law on this tradition? The study employs a field research method with a descriptive approach, incorporating syar’i (Islamic jurisprudence), cultural, and sociological perspectives. Data collection techniques include observation, interviews, and documentation to obtain relevant information about the issues studied. The findings reveal that: (1) The Peutron Aneuk ritual is performed on the seventh day after a baby's birth and includes several ceremonies, such as peucicap, peusijuk, beu kaca, balek hate manok, cuko 'ok, belah kelapa, peugiding tanoh, and marhaban. Each symbol in these rituals holds distinct philosophical meanings. (2) From the perspective of Islamic law, the Peutron Aneuk tradition practiced in Desa Paya Peunaga is considered inconsistent with Islamic teachings. This is due to the absence of explicit guidance from the Qur'an or the Sunnah mandating such practices. Additionally, the implementation of this tradition is not solely regarded as an expression of gratitude to Allah for the blessing of a newborn but also reflects a belief among some community members in the benefits of the tradition outside of Islamic values, which contradicts the principles of tawhid (Islamic monotheism).